IMPLEMENTATION OF RELIGIOUS VALUES ON INDIVIDUAL EDUCATION PROGRAM (IEP) BASED IN ISLAMIC ELEMENTARY SCHOOL - Kurniawan, Redite (JPK (Jurnal Pendidikan Khusus), 2019)
Elementary has emerged as an inclusive school in Indonesia recently. Eventhough some of them haven’t shown the proper planning of inclusive learning, learning process, and optimal outcome learning for special needs students. Moreover if the learning process connected with religious value in Islamic elementary school. How the implementation of religious value can be involved in Individual Education Program (IEP) in elementary school? This paper discuss about Individual Education Program (IEP) based on religious value which conduct as a particular curriculum for special needs students (SNS). Investigation for specific purpose on this study headed to Islamic values development in SNS. The data collected from interviews, documents, and observation from Ar-Roihan Inclusive Islamic Elementary School Lawang that has been pointed as inclusive pilot project since 2016. Prior study has shown the benefit of inclusive school for disability children, but it’s not focus on how Islamic values influence in their daily activities. Developed from data collected, the IEP program has reflected how the SNS used to and motivated to Islamic way in their daily activities, such as pray together, recite holy Qur’an, and respect for each other. Findings indicated that IEP which had given as individual treatment and lesson plan became an important thing for Islamic inclusive elementary school to reach their goal for disability students activities such as pray together, recite holy Quran, dan giving charity.